2015
DOI: 10.1109/lpt.2015.2438172
|View full text |Cite
|
Sign up to set email alerts
|

Co-Aperture Transceiving of Two Combined Beams Based on Adaptive Fiber Coupling Control

Abstract:  Abstract-We demonstrate the reception and transmission of fiber laser beams using two-element adaptive fiber-optics collimator (AFOC) array under simulated turbulences. Coupling efficiency of laser beam from free space into polarization maintaining fibers is optimized with tip/tilt aberration correction. According to the principle of optical reciprocity, tip/tilt errors of the phase-conjugated collimating laser beams are compensated simultaneously. The average of normalized coupling efficiency of one AFOC in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Tip/tilt control here coexists in the wavefront reconstruction procedure. When the power of the coupled laser beacon in each of the AFOC is maximized, subaperture tip/tilt errors have been also corrected for both the laser beams' receiving and transmitting functions of the AFOC array [23], [24]. Sub-aperture wavefront slope vector measured results could reveal the tip/tilt correction performance to some extent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tip/tilt control here coexists in the wavefront reconstruction procedure. When the power of the coupled laser beacon in each of the AFOC is maximized, subaperture tip/tilt errors have been also corrected for both the laser beams' receiving and transmitting functions of the AFOC array [23], [24]. Sub-aperture wavefront slope vector measured results could reveal the tip/tilt correction performance to some extent.…”
Section: Resultsmentioning
confidence: 99%
“…The voltages are amplified and drive the AFOCs to maximize the coupled metrics. As discussed in paper [23], the distorted wavefront could be recovered through the voltage values. The distorted phase we want to correct is brought by the glass plate with rough surface.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental results tell that the AFC system can further improve the coupling efficiency in both cases of the AO system off and on; however, the calibration of AFC system cannot be fully realized where the presence of higher-order aberrations make it difficult to detect the performance metrics. In addition, technical research of AFC array combined with the mentioned new algorithm is an ongoing effort in our group [14], [15], which is expected to solve the above problems in the future.…”
Section: Discussionmentioning
confidence: 99%
“…With the application of fiber-coupled array technology, researchers have found that the existing spatial light-fiber coupling scheme has disadvantages, such as poor reliability and inconvenient array expansion [11]. Moreover, the single-mode fiber (SMF) core diameter is very small (8-10 μm), and it is difficult to realize the coupling and alignment artificially [12].…”
Section: Introductionmentioning
confidence: 99%